2020
DOI: 10.1089/end.2019.0766
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Analgesic Effects of Preemptive Ultrasound-Guided Subcostal Transversus Abdominis Plane Block for Percutaneous Nephrolithotomy: A Prospective, Randomized Trial

Abstract: Background and Objectives: Percutaneous nephrolithotomy (PCNL) is a minimally invasive procedure for removing kidney stones, but patients still suffer from moderate postoperative pain. The aim of this study is to evaluate the perioperative analgesic effect of ultrasound-guided subcostal transversus abdominis plane (TAP) block performed before PCNL procedure. Materials and Methods: Patients scheduled for elective PCNL were randomized into two groups: Group TAP and Group IV. General anesthesia was induced with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Systemic opioids, nonsteroidal anti-inflammatory drugs (NSAIDs), and neuraxial methods such as epidural analgesia, paravertebral block, quadratus lumborum block (QLB), transversus abdominis plane (TAP) block, or local anesthetic infiltration along the nephrostomy tube can be employed to prevent postoperative pain caused by PCNL [5][6][7][8][9][10][11]. The use of NSAIDs is limited as these patients have potential renal problems.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic opioids, nonsteroidal anti-inflammatory drugs (NSAIDs), and neuraxial methods such as epidural analgesia, paravertebral block, quadratus lumborum block (QLB), transversus abdominis plane (TAP) block, or local anesthetic infiltration along the nephrostomy tube can be employed to prevent postoperative pain caused by PCNL [5][6][7][8][9][10][11]. The use of NSAIDs is limited as these patients have potential renal problems.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific findings support using paravertebral block or epidural anesthesia before PCNL to minimize the postoperative pain [16,17]. Local injection of analgesic drugs is also effective for this treatment [18][19][20][21]. Preventive preoperative intravenous or subarachnoid spinal analgesia was also described [22,23].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that it was inconsistent to determine the optimal time on TAP for patients undergoing surgeries. Some investigators recommended that TAP be performed before surgery [17,20,22]. Mansouri et al found that bilateral intrapleural block performed before cardiac surgery could get better analgesia than postoperative manipulation due to preemptive analgesia [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that it was inconsistent to determine the optimal time on TAP for patients undergoing surgeries. Some investigators recommended that TAP be performed before surgery [17,20,22], some preferred postoperative performance [15,16,23,24], and others found that there was no difference between the two time points.…”
Section: Introductionmentioning
confidence: 99%